Fifth World Congress of Sports Physical Therapy Scientific Abstracts - International Federation of Sports Physical Therapy; NFFs Faggruppe for Idrettsfysioterapi og Aktivitetsmedisin; International Journal of Sports Physical Therapy (International Journal of Sports Physical Therapy)
The International Journal of Sports Physical Therapy is pleased to publish abstracts from the 5th World Congress of Sports Physical Therapy, which will take place in Oslo, Norway, June 14-15, 2024. The theme of the Congress is “From Science To Clinical Practice.” The variety of presentations during this congress are examples of the contemporary sports physical therapy research activities taking place around the world.